Influence of the Catalytic Coke Formation on Reactor Surfaces in Thermal Cracking Process - Mohamadalizadeh, A.; Towfighi, J. (Asian Journal of Chemistry, 2010)
Knowledge of diffusion properties and reactions that taking place in thermal cracking reactors can result in better operations and decoking procedures leading to extension of the lifetime of furnace tubes. Formation of carbon on metal surfaces and catalysts is a problem in most hydrocarbon conversion processes. In this paper, after investigating a model for catalytic coke formation in reactors, some of the effects of coke formation on coils surfaces, such as the amount of the carbon diffused onto the surface and descending of the active site as well as the rate of the catalytic coke production was surveyed. The model also showed that the fact the amount of the diffused carbon is more compared with that of the released sites, confirming that the crystal diffusion consists of the controller factor for the rate of the catalytic coke production.